Hubungan Kesegaran Jasmani Dan Sikap Kerja Dengan Keluhan Muskuloskeletal Pada Pengrajin Manik Kaca Di Jombang - Wahyuni, Cahyani Asri (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
Objective: to identify the relation between physical fitness and work posture with musculoskeletal complaints in glass bead worker in Jombang. One of the prosess in making glass bead were forming process. Workers in forming part worked in un ergonomic posture for 8 hours everyday. Health effects that arised as a result of an unergonomic worked postures are musculoskeletal disorders.Otherwise, physical fitness also could effect musculoskeletal disorder complaint Methods: This article This researchÂ is an observational research with cross sectional approach design. The sample were 30 worker in forming part who fulfill inclusi category. Data were used Harvard Step Up Test, Rapid Entire Body Assessment (REBA), and filling out questionnaire Nordic Body Map (NBM). Correlation coeficient test was used to analyse the correlation between variables.Results: Â There was a strong corelation physical fitness and musculoskeletal complaints and physical fitness (correlation coefficient = 0,611) and modetare correlation between musculoskeletal complaints and work posture (correlation coefficient = 0,577).Conclusion: Based on the results of this study concluded that physical fitness and work posture were significantly related to musculoskeletal complaints. It is suggested to companies that provide picture of good work posture in workplace, so all workers would know about how to work with good posture. Keywords: Â physical fitness, work posture and musculoskeletal complaints